Optimation Of Protection Political Rights Disabled Persons As Fulfilment Of Legal Certainty In The Perspective Of Equality Before The Law - Verena Prameswari Sukoco (Faculty of Law, Universitas Negeri Semarang, 2025)
This article will discuss how the protection of political rights for people with disabilities is a fulfillment of the principle of consistency and certainty of election law that has been running so far. The research was conducted using a normative legal method through a statute approach. The writing of this article also takes the perspective of the principle of equality before the law or equality of standing in the eyes of the law. Basically, the democratic party, which is usually referred to as an election, is a means of realizing the sovereignty of the people, likewise with the political rights of its citizens, which are applied universally. Therefore, it should be noted that people with disabilities also have the same political rights as other citizens. However, in practice, there is still a lot of discrimination against people with disabilities in exercising their political rights in elections. Discrimination against people with disabilities reflects the inconsistency and uncertainty of the law in elections. Therefore, this article aims to assess, explain, and describe how to optimize the protection of political rights for people with disabilities as a fulfillment of the principle of consistency and certainty of election law from the perspective of equality before the law.